Interests in Petanque Sports Field Visitors Andi Makkasau Parepare City - Ade Yuni Sahruni; Priclya Margaretha Warwuru; Damaris Marlissa (Indonesian Journal of Physical Education and Sport Science)
Study Purpose. In this study the aim was to find out the interest in petanque sport by visitors to the Andi Makkasau field in Parepare City, which in general, petanque sport is a sport that is still commonplace but is seen as a positive activity for the community in striving to achieve at the level of physical fitness while also increasing achievement.